The economics of small-scale household pig production in Vietnam: Survey results, analysis and assessment - Que, N.N.; Lapar, Ma. Lucila; Tisdell, C.A.; Toan, N.N. (2012)
Vietnam relies heavily for its supply of pork (an important part of the Vietnamese diet) on small-scale household pig producers. Some Vietnamese policy makers believe this dependence to be uneconomical and favour the development of large-scale commercial piggeries to achieve potential economies of scale. To investigate whether Vietnamese household pig producers practice economies of scale, researchers from Center for Agricultural Policy (CAP) and International Livestock Research Institute (ILRI) surveyed 700 household pig producers from six provinces in Vietnam. After providing background on Vietnam’s pig industry and the survey design, this paper reports relevant results from this survey. The findings show that potential economic advantages due to greater scale did not strongly emerge from analysis of household survey data. On the other hand, potential economic benefits were observed among Vietnamese households from specialization in different stages of pig production. In assessing the economics of household pig production, it is important to take into account the opportunity costs of the resources used in this production. Given the current stage of Vietnam’s economic transition, the opportunity cost of the labor employed in household production seems to be low. Furthermore, small-scale producers depend more heavily on home-grown and local produce for pig food compared to larger producers who are more reliant on processed pig food with an imported content. Low opportunity costs continue to make small-scale household pig production in Vietnam economical but with continuing economic development, the opportunity costs of agricultural households will increase. Larger-scale commercial producers will thus, likely account for a growing proportion of Vietnam’s pig supply, particularly given current policies in their favour. Currently, it is still economical for both household and large-scale pig producers to supply the market.